2015
DOI: 10.1002/sec.1289
|View full text |Cite
|
Sign up to set email alerts
|

Compression and encryption for remote sensing image using chaotic system

Abstract: In this paper, because of the acquisition principle and big data of remote sensing image, we suggest an encryption scheme using chaotic system to build up the compressed sensing framework. A two‐dimensional generalized Arnold map is adopted here to generate the entries of the Toeplitz matrix used as measurement matrix. Then, the selecting row of the Toeplitz matrix is also decided by the chaotic sequence generated randomly by the Arnold map. With a further function of permutation operation, we can also encrypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…I. Scrambling is performed on the measurements, such as [20], [21]; II. Scrambling is done in the frequency domain, such as [22], [25].…”
Section: B Scrambling In the Measurements Domain Or The Frequency Domentioning
confidence: 99%
See 1 more Smart Citation
“…I. Scrambling is performed on the measurements, such as [20], [21]; II. Scrambling is done in the frequency domain, such as [22], [25].…”
Section: B Scrambling In the Measurements Domain Or The Frequency Domentioning
confidence: 99%
“…In [20], Zeng et al proposed a speech encryption algorithm by scrambling the CS measurements. A similar idea was later applied for secure remote image sensing [21]. For the purpose of image acquisition and confidentiality, Zhang et al [22] suggested scrambling the frequency coefficients before the CS encoding instead of scrambling the CS samples.…”
Section: Introductionmentioning
confidence: 99%
“…Arnold's cat map is invertible [10,11,13]. This is important, because it allows the image to be retrieved during the decryption process.…”
Section: Introductionmentioning
confidence: 99%
“…An image encryption algorithm was proposed by combining the DCT with 2D chaotic map to solve the problem of poor security and small key space in one-dimensional chaotic cryptosystems [31]. In 2015, an image compression and encryption algorithm was devised, in which the chaotic system was employed to generate pseudo-random measurement matrices [32]. To further improve the security and the compression performance of image encryption schemes, TONG et al presented a color image compression and encryption scheme based on the hyper-chaotic system, where the dictionary of discrete cosine transform was exploited to represent the color image sparsely [33].…”
Section: Introductionmentioning
confidence: 99%